Akibat Hukum Terhadap Tidak Dilakukan Penghapusan (Roya) Jaminan Fidusia Setelah Kredit Lunas - Ni Putu Sawitri Nandari; Dewa Krisna Prasada; Kadek Julia Mahadewi; Tania Novelin; Dewa Ayu Putri Sukadana (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2023)
Legal obligation is an action that must be done by someone. Every action taken is a form of a sense of responsibility for the problems that are happening, be it legally or morally. Therefore, obligations will always be attached to human life in carrying out social activities. Rules regarding the obligation for fiduciary recipients to carry out fiduciary write-offs (roya) if the agreed debt has been paid off, but it is also necessary to know about the legal consequences if the obligation to write-off (roya) fiduciary guarantees is not carried out, it can result in losses for the fiduciary giver. In this case the problem arises